STUDIES ON FISHES SPECIES DIVERSITY OF RIVER HADEJIA JIGAWA STATE NIGERIA - YOLA, I. A.; B. MUHAMMAD (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
The aim of the research was to study the abundance and diversity of fish in river Hadejia. The study was carried out from April to September, 2016. The fishing sites were Marke, Dingare and Hadejia-barrage. Data collection was done on monthly basis taking length and weight of fishes, using standard procedure and key for identification. Two hundred and twenty-five (225) fishes were sampled comprising twenty (20) genera belonging to fourteen (14) families. The families identified included: Bagridae, Centropomidae,Characidae,Cichlidae, Citharidae, Lariidae, Cyprinidae, Malapturidae, Mochochidae, Lepidoserinidae, Mormyridae, Osteoglossidae, Polypteridae, and Shilbeidae. The family Mormyridae has the highest genera. River Hadejia has high diversity of fishes as indicate by the Shannon wiener diversity index of 2.93 and the population evenness of average 0.98 in all the landing sites as well as Menhinick richness of average 2.35, these can be confirmed as the twenty-two species of commercial importance were recorded.